Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
e) 9x - 3x = 7 + 5
6x = 12 / ÷6
x = 2
Spr. 9 · 2 - 7 = 3 · 2 + 5
18 - 7 = 6 + 5
11 = 11
f) - 10x + 4x = 9 - 3
- 6x = 6 / ÷ ( - 6)
x = - 1
Spr. 3 - 10 · ( -1) = 9 - 4 · ( -1)
3 + 10 = 9 + 4
13 = 13
g). - 2x + 6x = 9 - 5
4x = 4 / ÷ 4
x = 1
Spr. 5 - 2 · 1 = 9 - 6 · 1
5 - 2 = 9 - 6
3 = 3
h) 4x - 5x = 4 + 6
- x = 10 / · ( -1)
x = - 10
Spr. - 6 + 4 · ( - 10) = 5 · ( - 10) + 4
- 6 - 40 = - 50 + 4
- 46 = - 46
Odpowiedź:
e) 9*x-7=3*x+5
9x-7=3x+5/-3x
6x-7=5/+7
6x=12/:6
x=2
Sprawdzenie:
9*2-7=3*2+5
18-7=6+5
11=11
f)3-10*x=9-4*x
3-10x=9-4x/+4x
3-6x=9/-3
-6x=6/:-6
x=(-1)
Sprawdzenie:
3-10*(-1)=9-4*(-1)
3+10=9+4
13=13
g)5-2x=9-6x/+6x
5+4x=9/-5
4x=4/:4
x=1
Sprawdzenie:
5-2*1=9-6*1
5-2=9-6
3=3
h)-6+4x=5x+4/-4x
-6=x+4/-4
x=(-10)
Sprawdzenie:
-6+4*(-10)=5*(-10)+4
-6 -40=(-50)+4
-46=(-46)
Szczegółowe wyjaśnienie: